SEBARAN KONDISI SANITASI LINGKUNGAN DENGAN KEJADIAN DIARE PADA BALITA MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KECAMATAN SEMARANG SELATAN - Fachrizal Ganiwijaya; Mursid Raharjo; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Diarrheal disease is still one of the major causes of morbidity and mortality. In Indonesia morbidity of diarrhea in 2002 of 6.7 per 1,000 population, while in 2003 increased to 10.6 per 1,000 population. Diarrheal disease is a disease that based environment. Geographic information systems can be used to create a map of their health and get information epidemiological data. The function of this research is to drawing distribution of event about diarrhea on children under five years and the condition of sanitation in the district of South Semarang. The total sample of 42 samples of children under five years in the District of South Semarang. The analysis used in this study were univariate, bivariate, and coordinates. Type of research is observational with cross sectional design. The results showed a significant relationship between the type of clean water sources with the incidence of diarrhea in children under five years (p-value = 0.001). There is no relationship between the quality of drinking water with the occurrence of diarrhea in children under five years (p-value = 0.094). There is a correlation between the condition of toilets to the occurrence of diarrhea in children under five years (p-value = 0.001). There is a correlation between the condition of garbage disposal facilities with the incidence of diarrhea in children under five (p-value = 0.001). The conclusion of this study a greater proportion of infant diarrhea, the proportion of respondents using well water is smaller, the proportion of drinking water quality are E. coli smaller proportion of latrine facility conditions that do not qualify are smaller, the proportion of waste disposal facility conditions that do not qualify smaller, there is a correlation between the types of sources of clean water, toilet facilities condition, and the condition of garbage disposal facilities with diarrhea on children under five years. There was no relation between quantity of drinking water with diarrhea incidence of children under five years.